2022
DOI: 10.1097/tme.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Nurse Practitioner and Physician Assistant Burnout, Perceived Stress, and Utilization of Wellness Resources During 2020 in a Large Urban Medical Center

Abstract: The objectives of this study were to measure perceived stress, burnout, and utilization and perceived benefit of wellness practices among emergency medicine (EM) nurse practitioners (NPs) and physician assistants (PAs). An additional aim was to evaluate attributions of stress to racism and the COVID-19 pandemic. A 28-item electronic survey of ED NPs/PAs at 3 hospitals was used to measure respondents' perceived stress (Perceived Stress Scale), stress attributed to COVID-19 and systemic racism, burnout (2-item m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…11 Similarly, Seitz and colleagues, who investigated burnout in emergency medicine APPs, found that 58.5% of respondents reported burnout from their job, but were limited by 53 participants and a response rate of 42.4%. 12 Edwards et al also found that burnout was more likely in those who worked in the hospital- or health system-owned practices compared to those working in private practice. 13 Additionally, increased age and working full-time compared to part-time was associated with significantly higher depersonalization scores.…”
Section: Discussionmentioning
confidence: 98%
“…11 Similarly, Seitz and colleagues, who investigated burnout in emergency medicine APPs, found that 58.5% of respondents reported burnout from their job, but were limited by 53 participants and a response rate of 42.4%. 12 Edwards et al also found that burnout was more likely in those who worked in the hospital- or health system-owned practices compared to those working in private practice. 13 Additionally, increased age and working full-time compared to part-time was associated with significantly higher depersonalization scores.…”
Section: Discussionmentioning
confidence: 98%
“…25 İş ilişkili faktörler için literatürde iş yoğunluğu, bağımsız karar verme gibi faktörlerin stres üzerinde anlamlı fark oluşturduğu ancak eğitim düzeyi gibi faktörlerin stres üzerinde fark oluşturmadığı raporlanmıştır. 26,27 Çalışılan birimdeki iş yoğunluğu ve alınan sorumlulukların fazlalığı stresi artıran faktörler arasındadır. Örneğin yoğun bakım gibi daha karmaşık işlerin olduğu, teknolojik uygulamaların bulunduğu ve komplike hastalara bakım verilen birimlerde çalışan hemşirelerde stres düzeyleri daha fazladır.…”
Section: Discussionunclassified
“… 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 High levels of clinician burnout may also be a barrier, as burnout levels among ED physicians and nurses have been exacerbated by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic. 26 , 27 , 28 …”
Section: Introductionmentioning
confidence: 99%
“…Research studies implementing temporary social needs screening in EDs suggest that similar barriers likely exist, with additional barriers of illness acuity and unique ED workflow constraints 15,17–25 . High levels of clinician burnout may also be a barrier, as burnout levels among ED physicians and nurses have been exacerbated by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic 26–28 …”
Section: Introductionmentioning
confidence: 99%